Support for Families of Youths and Adults with Intellectual Disabilities: Contributions of a Program from Families' and Specialists' Perspectives - Maria Villaescusa; Natxo Martínez-Rueda; Almudena Fernández (MDPI AG, 2021)
A family-centered approach (FCA) is recognized as a set of values, principles, and practices aimed at strengthening families' abilities to promote the development and well-being of its members. Despite the limited information available, results show the positive relationship between the support model, based on the collaboration between families and specialists, and family empowerment. This paper seeks to analyze the opinions of families and specialists on their participation in an intervention program for families of youths and adults with disabilities. Thirteen families and eight specialists participated in the study that used qualitative techniques, such as interviews and discussion groups, and a questionnaire to gather information about the families' and specialists' viewpoints over one year. Results show that families welcomed their involvement in the program. Both families and specialists recognize that creating a space for the whole family is the main contribution of the program, as it highlights the importance of considering the family's entire system as a support unit, as well as the close relationship between the individual's and family's quality of life (FQoL).